Zooplankton assemblage structure and diversity since pre‐industrial times in relation to land use. Issue 11 (9th August 2022) - Paquette, Cindy; Griffiths, Katherine; Gregory‐Eaves, Irene; Beisner, Beatrix E.
Abstract: Aim: While it is now well accepted that human activities are having pronounced effects on natural ecosystems, regional variation in the rate and magnitude of various human impacts is unclear. Moreover, the effects of land use change on natural aquatic communities have only relatively recently begun to be explored. Our goal was to understand how and where assemblages of a central food web component of freshwater lakes have changed over the course of industrialization in relation to land use. Location: Canada. Time period: Pre‐1880 AD to present. Major taxa studied: Cladoceran zooplankton. Methods: As part of the Natural Sciences and Engineering Research Council (NSERC) Canadian Lake Pulse Network, we selected 101 lakes across Canada along a gradient of human impact to analyse subfossil cladoceran assemblages from sediment cores. We examined relationships between taxonomic and functional indicators of cladoceran assemblage change among lakes and through time. Results: Contemporary assemblages were taxonomically and functionally less diverse locally relative to pre‐industrial assemblages (α‐diversity) and were structured by the degree of human impact in watersheds. Local α‐diversity losses were greatest in highly impacted lakes where agriculture and pasture are prevalent. While spatial homogenization (spatial β‐diversity) did not increase since pre‐industrial times as expected, temporal turnover (temporal β‐diversity) showed a non‐significant but increasing trend in highly impacted lakes, especially in urbanized watersheds. Main conclusions: Cladoceran assemblages have changed significantly over the course of the Industrial period, and especially in more highly impacted watersheds, underscoring the important role of watershed land use in shaping diversity. However, indicators of cladoceran function have remained relatively conserved over time and land use change showed little impact on β‐diversity, despite important environmental variation. Overall, this research furthers our understanding of the health status of Canadian lakes and the consequences of human activities, especially agriculture and urbanization, on lake zooplankton.